Role of m6A methyltransferase component VIRMA in multiple human cancers (Review) - Zhu, Wei; Wang, Jing-Zi; Wei, Ji-Fu; Lu, Chen (Cancer cell international, 2021)
N 6-Methyladenosine (m6A) modification is one of the most widely distributed RNA modifications in eukaryotes. It participates in various RNA functions and plays vital roles in tissue development, stem cell formation and differentiation, heat shock response control, and circadian clock controlling, particularly during tumor development. The reversible regulation of m6A modification is affected by the so-called ‘reader’, ‘writer’ and ‘eraser’. As a required component and the largest methyltransferase, vir-like m6A methyltransferase associated (VIRMA) can promote the progression of cancer and is associated with poor survival in multiple types of cancer. The present review investigated the role of VIRMA in various types of cancer. In an m6A-dependent or -independent manner, VIRMA can play an oncogenic role by regulating cancer cell proliferation, migration and invasion, metastasis, apoptosis resistance and tumor growth in different pathways by targeting stem factors, CCAT1/2, ID2, GATA3, CDK1, c-Jun, etc. VIRMA can also predict better prognosis in kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP) and papillary thyroid carcinoma by TCGA analysis. The obvious oncogenic roles of VIRMA observed in different types of cancer and the mechanisms of VIRMA promoting cancers provided the basis for potential therapeutic targeting for cancer treatments.